Physicians' Earnings Do Not Affect Their Online Ratings - Haffey, Sean C.; Hopman, Wilma M.; Leveridge, Michael J. (Frontiers in Public Health, 2020)
Objective: Physician-rating websites have exploded in popularity in recent years. Consequently, these sites have garnered attention from researchers interested in factors influencing patient satisfaction. A doctor’s earnings might reflect practice patterns that could influence their patients’ perceptions. We sought to explore any association between physicians’ earnings and their online ratings. Methods: The names and billings of 500 physicians from British Columbia, Canada were randomly extracted from the 2016-17 BC Blue Book and matched to their profiles on RateMDs.com. Physicians’ earnings were compared to their global ratings and to their Staff, Punctuality, Helpfulness and Knowledge scores. Earnings and ratings were also compared between men and women. Results: We found no significant correlation between physicians’ earnings and their global online ratings (p=0.304). Weak negative correlations existed between earnings and Staff and Helpfulness ratings (Spearman’s rho = -0.055, p<0.001; rho = -0.033, p<0.028). Online ratings were largely favorable (mean MD rating of 3.85/5. Male physicians earned significantly more than their female colleagues (371,734.85 and 261,590.82, respectively; p<0.001), but no significant difference existed between men and women with regards to online ratings (mean 3.87 and 3.81, respectively, p=0.191). Conclusions: No meaningful association was found between physicians’ earnings and their online ratings. Patients tend to review doctors favorably online; these data add to the discussion of whether male and female doctors are differentially rated. Trends towards increased transparency in health care systems may help to elucidate how doctors’ earnings influence patients’ perception of and satisfaction with the care they receive.